Budget Efficiency as a Regional Financial Management Strategy : (Case Study of the Central Kalimantan Provincial Government's Regional Budget) - Adi Tya Indrawan; Andriansyah; Novianita Rulandari (Ilomata International Journal of Social Science, 2026)
This study aims to analyze the implementation of budget efficiency policies as a regional financial management strategy in the Central Kalimantan Provincial Government for the 2021–2025 period. The study focuses on budget trends and revenue realization, expenditures, efficiency ratios, and the performance of Regional Original Revenue (PAD) components. The research method used is a qualitative case study approach, involving documentation, in-depth interviews, and direct observation at relevant agencies, namely the Finance Bureau of the Regional Secretariat and the Central Kalimantan Provincial Development Planning Agency (Bappeda). The results show that although fiscal capacity has experienced significant growth, the percentage of expenditure realization remains below the ideal target, with efficiency ratios varying between 82.69% and 109.55%. Improved regional tax performance is the main factor in strengthening PAD, while regional levies and regional wealth management results still show low performance. The implemented efficiency policies have succeeded in saving non-priority expenditures without sacrificing basic service sectors, in line with the principle ofvalue for money And good governanceHowever, key challenges include limited human resource capacity, a suboptimal integrated budgeting information system, and bureaucratic resistance to budget restructuring. This research contributes theoretically to the literature on provincial-level budget efficiency and offers practical recommendations for other regions to optimize budget allocation, strengthen fiscal independence, and maintain the quality of public services sustainably.